Conflict and compromise: the Premonstratensians of Ninove (Flanders) and the laity in the twelfth century. - Bijsterveld, Arnoud-Jan A. (Negotiating Secular and Ecclesiastical Power: Western Europe in the Central Middle Ages, 1999)
Investigates what the miracle stories in the Liber miraculorum s. Cornelii Ninivensis can reveal about relations between the canons and the laity, expecially the way in which they dealt with the laity in conflicts
Keywords: ninove

Gift Exchange, Landed Property, and Eternity: the Foundation and Endowment of the Premonstratensian priory of Postel (1128/1138-1179) - Bijsterveld, Arnoud-Jan A. (Land and ancestors: cultural dynamics in the Urnfield period and the Middle Ages in the Southern Netherlands, 1999)
Keywords: postel

Magnetization dating at a medieval monastery (Tupholme, Lincolnshire) - Borradaile, Graham John (Archaeometry, 1999)
Keywords: tupholme

Whithorn Priory in the Late Middle Ages - Dilworth, G. Mark (Friends of the Whithorn Trust, 1999)
Keywords: whithorn

Barnard Castle, County Durham : Egglestone Abbey, North Yorkshire : Bowes Castle, North Yorkshire - Kenyon, Katy; Poultney, Lorimer (English Heritage, 1999)
Keywords: egglestone